World mythology/ edited by Roy Willis - "Willis, Roy(ed.)" (London, 2006)
World Mythology" is a wide-ranging collection of the most important mythological traditions, combining the impact of pure narrative with the background necessary for understanding. Superbly illustrated throughout, this is the most accessible guide yet produced to the limitless heritage of the world's imagination. Under the direction of Dr Roy Willis, nineteen leading scholars have distilled the essence of each regional tradition. Each contributor navigates a clear path through the complexities of myth by focusing on the most significant figures and stories, within a series of thematic essays. The selected mythical episodes - the downfall of gods and demons, stories of revenge and metamorphosis, tales of doomed love and travels to the Underworld - are told at length in special highlighted features.
Keywords: Mythology